Study of Solar Combined Air Energy Greenhouse Heating System Model - Hao, Wang; Jintao, Wei; Ruifeng, Zhang; Zhenjun, Xu (Frontiers in Energy Research, 2022)
At present, it is difficult to bring centralized heating to rural areas owing to factors such as scattered distribution, distance from towns and cities, and difficulty in laying public pipes. According to research, most rural residents use inefficient household heating facilities, thereby resulting in serious environmental pollution and a decline in the quality of life of residents. In order to alleviate environmental pollution, the use of solar energy, air energy, and other renewable energy for rural heating of such decentralized buildings is of profound significance. This study analyzed the distribution characteristics of solar energy resources and solar combined air energy greenhouse heating system, established and solved a mathematical model of the solar combined air energy greenhouse heating system, calculated solar heat collection and solar heating energy consumption. From the data analysis, the relationship among heat gain power, heating power, and the water temperature of the water storage tank of the heat pump system was obtained. The mathematical model of the storage tank of the solar combined air energy greenhouse heating system was solved, and the operating conditions and volume of the storage tank of the solar combined air energy greenhouse heating system were determined. The study also analyzed the solar heat collection and solar heating energy consumption in Qingdao, thereby pointing out the advantages of the solar combined air energy greenhouse heating system, and finally obtained the best heating scheme.